Rosuvastatin in patients with arterial hypertension and dyslipidemia: effects on microcirculation and pulse wave parameters - O. M. Drapkina; O. N. Korneeva; L. O. Palatkina; E. V. Zyatenkova; N. P. Balakhonova; V. T. Ivashkin (Кардиоваскулярная терапия и профилактика)
Aim. To investigate the parameters of pulse wave contour analysis (PWCA) and microcirculation (MC) in patients with arterial hypertension (AH), dyslipidemia (DLP), and high cardiovascular risk levels (SCORE >5%); to compare the dynamics of these parameters during the treatment with rosuvastatin or atorvastatin. Material and methods. The study included 82 patients (mean age 53±10 years) with the high-risk AH (SCORE levels >5%), DLP, and no strict contraindications to statins. All patients were randomised into two comparable groups: Group I (n=40; mean age 51±10 years), receiving atorvastatin and standard AH treatment; and Group II (n=42; mean age 52±10 years), receiving rosuvastatin and standard AH treatment. At baseline and after 5 weeks, all patients underwent the MC assessment (conjunctival biomicroscopy) and PWCA (AngioScan-01). The following parameters were assessed: stiffness index (SI), reflection index (RI), augmentation index (AIx), and increased pulse wave amplitude (PWA). Results. In the atorvastatin group, mean SI values were 5,87±2,05 m/s, RI values 35,64±19,98%, mean AIx values for heart rate of 75 beats per minute (AIx75) 41,21±14,56%, and mean central blood pressure (BP, Spa) levels 144,35±22,31 mm Hg. In the rosuvastatin group, the respective values were 5,01±2,56 m/s (SI), 37,01±14,56% (RI), 41,23±14,35% (AIx75), and 148,98±7,89 mm Hg (BP, Spa). All participants demonstrated PW Types A and B, as a marker of increased arterial stiffness, and positive AIx and AIx75 values. The treatment with atorvastatin and rosuvastatin was associated with a significant reduction in ∆SI (-0,87 and -0,89 m/s, respectively). Both groups demonstrated a non-significant reduction in ∆RI (-7,89 and -7,21%, respectively) and ∆AIx (-1,88 and -1,92%, respectively). PWA increased by 1,82±0,62 times in the atorvastatin group and by 1,95±0,81 times in the rosuvastatin group. At baseline, both groups demonstrated disturbed conjunctival MC (arterio-venular coefficient 1:3, stasis, and Stage III erythrocyte aggregation). Atorvastatin and rosuvastatin treatment was linked to a regression in the last two parameters, which could be explained by the improved vascular wall elasticity. Conclusion. In high-risk patients with AH, the PWCA data suggested an increase in arterial stiffness, which was combined with conjunctival MC disturbances. Statin therapy improved not only blood lipid levels, but also MC, vascular stiffness, and endothelial function parameters, which was more pronounced in the rosuvastatin group.